Risk Factors of Recurrent Febrile Convulsions in Children in AL-batool Teaching Hospital - Hailah Othman Habeeb (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Febrile seizures are the most common convulsive disorder in infants and children. Its occurbetween the age of 6 and 60 mo.There are two type of febrile convulsion simple and complex; A simplefebrile seizure is a primary generalized, usually tonic-clonic, attack associated with fever, lasting for amaximum of 15 min, and not recurrent within a 24-hour period. A complex febrile seizure is more prolonged(>15 min), focal, and/or recurs within 24 hr .Aim of the study: To identify the risk factors for recurrence of febrile convulsions in children.Materials and Methods: This was a case-controlled study done at Al Batool teaching hospital .Studyconducted over a period of five months , from August 2018 to December 2018 . All children with febrileseizure belonging to age group of 6 months to 6 years were included in the study.Results : Compared to children with first attack of febrile convulsion, children with recurrent seizures wereyounger at onset (12_24mo.) (26% vs. 54%), mainly male (72% vs. 62%) and had more often family history(second degree relative), low degree of temperature (78% vs. 36%),simple febrile convulsion (52% vs.68%),duration of fever less than12 hours (78% vs. 70%), and frequent febrile illnesses (74% vs. 20%). firstdegree family history of febrile convulsion and family history of epilepsy were not significant risk factors.Conclusions: The risk factors associated with increased incidence of recurrence FC are: male sex, agebetween12_24 months at the onset of the first FC, family history of FC in a second degree relative, durationof fever <12 hours ,simple type of convulsion &frequent attack of febrile illness(>4per year).